The Relationship Of Postpartum Mother's Knowledge With Giving Colostrum To Babies - Hirawani, Mutia (Cattleya Darmaya Fortuna, 2022)
Colostrum, the initial fluid secreted by the breasts during early lactation, is renowned for its superior immune-boosting properties, offering crucial protection to newborns against diseases. This study aimed to investigate the association between postpartum maternal knowledge and the provision of colostrum to infants. Utilizing an analytical survey approach, the research involved a population of 37 postpartum mothers. Random sampling was employed to select 37 respondents from the total population. The research instrument comprised a primary data collection tool in the form of a questionnaire consisting of 20 statements. Data processing involved editing, coding, tabulating, and scoring. Findings revealed that the majority of respondents exhibited inadequate knowledge, with 16 respondents (55.0%) scoring below the desired threshold. Statistical analysis using the chi-square test indicated a significant relationship between postpartum mothers' knowledge and the practice of colostrum provision (p-value = 0.044 < 0.05), leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis. This study underscores the importance of enhancing maternal knowledge regarding colostrum provision, particularly in the context of the Nurkholida Darussalam Midwife Clinic, Panyabungan District, Mandailing Natal Regency. It is recommended that clinic leadership actively engage in educational initiatives to elucidate the benefits of colostrum, ultimately promoting optimal infant health outcomes.